Impact of Fungal Co-Infection on Teicoplanin Plasma Trough Concentration in Critically Ill Adults: A Novel Consideration for Dose Adjustment - Cheng L; Wang L; You X; Xiong L; Dai Q; Wang Q (Drug Design, Development and Therapy, 2025)
Lin Cheng,1,* Lina Wang,2,* Xi You,1 Lirong Xiong,1 Qing Dai,1 Qian Wang1 1Department of Pharmacy, The First Affiliated Hospital of Army Medical University, Chongqing, People’s Republic of China; 2Department of Obstetrics and Gynecology, The First Affiliated Hospital of Army Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing Dai, Email dq050@tmmu.edu.cn Qian Wang, Email wangqian411@tmmu.edu.cnObjective: The pathophysiology and disease status of critically ill patients have a significant impact on the pharmacokinetics/pharmacodynamics (PK/PD) of antimicrobial agents. However, the effect of fungal co-infection on the plasma trough concentration (Cmin) of teicoplanin in critically ill patients remains unclear.Materials and Methods: A retrospective cohort study was carried out. Clinical data of patients admitted to the intensive care unit and receiving teicoplanin therapeutic drug monitoring were collected. Multiple linear stepwise regression analysis and binary logistic regression analysis were used to identify the factors influencing teicoplanin Cmin and the achievement of the target Cmin (≥ 15.0 μg/mL).Results: A total of 404 teicoplanin Cmin values from 231 patients were included. The mean teicoplanin Cmin was 20.63 ± 10.40 μg/mL, and the percentage of Cmin > 30.0 μg/mL was 15.8%. In the multivariate analysis, fungal co-infection was identified as an independent factor affecting teicoplanin Cmin (B=4.056, 95% CI 2.089– 6.023; p< 0.001) and the attainment of the target Cmin (OR=3.233, 95% CI 1.538– 6.795; p=0.002). Sex, weight, teicoplanin dose, levels of direct bilirubin, blood urea nitrogen, estimated glomerular filtration rate, and uric acid were also found to be influencing factors. Patients with fungal co-infection had a higher teicoplanin Cmin (p< 0.001) and a higher percentage of Cmin > 30.0 μg/mL (20.3% vs 12.0%; p=0.022) compared to those without, despite similar teicoplanin doses (p=0.302). The percentage of patients receiving continuous renal replacement therapy was higher in the fungal co-infection cohort (p=0.016), along with an older age and a lower body weight.Conclusion: For critically ill patients with fungal co-infections, the teicoplanin dose should be decreased, or at least not increased. This is essential for reducing the potential risk of toxicity and customizing dosing strategies to meet individual patient needs. A large-scale, multi-center, prospective study is necessary to confirm the findings related to this dosing approach.Keywords: teicoplanin, critically ill patients, therapeutic drug monitoring, fungal infection, direct bilirubin